Multimodal nanoparticles as alignment and correlation markers in fluorescence/soft X-ray cryo-microscopy/tomography of nucleoplasmic reticulum and apoptosis in mammalian cells. - Hagen, C; Werner, S; Carregal-Romero, S; N Malhas, A; G Klupp, B; Guttmann, P; Rehbein, S; Henzler, K; C Mettenleiter, T; J Vaux, D; J Parak, W; Schneider, G; et al. (Elsevier, 2014)
Correlative fluorescence and soft X-ray cryo-microscopy/tomography on flat sample holders is perfectly suited to study the uncompromised physiological status of adherent cells at its best possible preservation by imaging after fast cryo-immobilization. To understand the mechanism by which herpesviruses induce nucleoplasmic reticulum, i.e. invaginations of the nuclear envelope, during their egress from the host cell nucleus, morphologically similar structures found in laminopathies and after chemical induction were investigated as a potentially more easily accessible model system. For example, anti-retroviral protease inhibitors like Saquinavir also induce invaginations of the nuclear membranes. With the help of newly designed multimodal nanoparticles as alignment and correlation markers, and by optimizing fluorescence cryo-microscopy data acquisition, an elaborate three-dimensional network of nucleoplasmic reticulum was demonstrated in nuclei of Saquinavir-treated rabbit kidney cells expressing a fluorescently labeled inner nuclear membrane protein. In part of the protease inhibitor-treated samples, nuclei exhibited dramatic ultrastructural changes indicative of programmed cell death/apoptosis. This unexpected observation highlights another unique feature of soft X-ray microscopy, i.e. high absorption contrast information not relying on labeled cellular components, at a 3D resolution of approximately 40 nm (half-pitch) and through a sample thickness of several micrometers. These properties make it a valuable part of the cell biology imaging toolbox to visualize the cellular ultrastructure in its completeness.